Corporate Growth Potential in Value of Banking Companies Listed on The Indonesia Stock Exchange 2015-2021 - Labo, Irwan Adam (International Journal Labs, 2023)
This study investigates the impact of a Company's Growth Potential on Firm Value, with a specific focus on empirical testing and analyzing the relationship between the variables. The research was carried out at the Indonesia Stock Exchange, concentrating on banking companies as the primary objects of observation. The observation period spanned from 2015 to 2021. In this study, the population consisted of 46 companies, and a sample of 10 companies was selected for detailed examination. The researchers aimed to measure the influence of the Company's Growth Potential, serving as a proxy for the Investment Opportunity Set (IOS), on the firm value of these selected entities. The results of the analysis revealed a significant and positive impact of the Company's Growth Potential on the firm value of the observed banking companies. This finding suggests that higher growth potential positively correlates with increased firm value, indicating that companies with promising investment opportunities tend to have higher market valuations. These findings contribute to the existing literature on corporate finance and provide valuable insights for investors, financial analysts, and decision-makers in the banking sector. The study underscores the importance of considering growth potential as a key indicator when evaluating the firm's value and investment opportunities within the dynamic landscape of the Indonesia Stock Exchange. Further research could expand on these findings and explore other factors influencing firm value in different industries or regions.